Pengaruh Penggunaan Media Video Youtube terhadap Kreativitas dan Hasil Belajar Pendidikan Agama Islam pada Materi Kaligrafi (Tahsin Al-Khat) Kelas XII OTKP di SMK PGRI 5 Jember - Sari, Indiana Purnama (Asian Journal of Islamic Studies and Da'wah, 2024)
Creativity is greatly influenced by the environment, therefore there is a need for active learning that can lead to interaction between students and student interaction with dynamic elements in learning. The dynamic elements referred to here emphasize more on the use of media in learning. This research aims to determine the influence of YouTube media on creativity and learning outcomes in Islamic Religious Education at SMK PGRI 5 Jember. This research uses a quasi-experimental method with the type of research being quantitative. The data collection technique used was purpose sampling with questionnaires, tests and documentation. Meanwhile, data analysis uses the T-test. This research succeeded in concluding that YouTube video media has a significant influence on creativity and learning outcomes in Islamic Religious Education. It is proven from the calculation results that the average creativity of experimental class students was 74.47 and then increased to 89.63, while in the control class it was found that student creativity was 74.87 to 85.40. Likewise, based on the t test using the Independent Sample T Test, it shows that the sig value. 0.035 < 0.05 so the first Ha is accepted. And based on the results of the t test using the Independent Sample T Test, it shows that the sig. 0.022 < 0.05 so the second Ha is accepted. In the third Ha, the data shows that YouTube video media together influences creativity and learning outcomes in Islamic Religious Education.